Modular study table - Wan Mohd Firdaus, Wan Mohd Nor (2009)
The problem to the existing table nowadays is it is fix or limited to number of person that can use it in the same time. The space for it cannot be adjusted to accommodate more people then it supposed to. The user has to find other solution such as providing another table if the current table cannot fulfill the number of people. The purpose of this project is to design and develop a study table that can be manipulated in term of the space that the table can provide according requirement. In this project, the table would be able to support amount of user from single person till four person max at a time. The use of the table can be modulated from a single person to a group of four people. Single person would use smaller space compared to a group of four people. The variable condition makes the usage requirement varies from time to time. The objective of this project is to design, analyse the structure and lastly to fabricate the flexible table that can fill the needs from user. The scope of work is to draw the parts for the table by using Solidworks software, assemble all the parts into a table in the Solidworks, build the real structure of the table (by parts), and use the ALGOR software to analyse the structure. In the analysis, it is mainly to determine the value of maximum yield stress the table can support for each case from single person study table to maximum four person study table. In the analysis, the maximum value from software analysis is 107.866MPa, happens in the four person usage case. The value is acceptable due to the yield strength of the material used, aluminum, is 325MPa. Displacement for the structure can also be observed in ALGOR analysis for all three cases. Displacement of 9.4mm is observed in simulation for four person usage and this value is still acceptable for construction. The table did form the shape planned but the surface of the table tend to bend even without the load. The deformation can clearly spotted visually relative to a straight object.